Seismic rupture during the 1960 Great Chile and the 2010 Maule earthquakes limited by a giant Pleistocene submarine slope failure. (25th June 2013) - Geersen, Jacob; Völker, David; Behrmann, Jan H.; Kläschen, Dirk; Weinrebe, Wilhelm; Krastel, Sebastian; Reichert, Christian
Abstract: Determining factors that limit coseismic rupture is important to evaluate the hazard of powerful subduction zone earthquakes such as the 2011 Tohoku‐Oki event (Mw = 9.0). In 1960 (Mw = 9.5) and 2010 (Mw = 8.8), Chile was hit by such powerful earthquakes, the boundary of which was the site of a giant submarine slope failure with chaotic debris subducted to seismogenic zone depth. Here, a continuous décollement is absent, whereas away from the slope failure, a continuous décollement is seismically imaged. We infer that underthrusting of inhomogeneous slide deposits prevents the development of a décollement, and thus the formation of a thin continuous slip zone necessary for earthquake rupture propagation. Thus, coseismic rupture during the 1960 and 2010 earthquakes seems to be limited by underthrusted upper plate mass‐wasting deposits. More generally, our results suggest that upper plate dynamics and resulting surface processes can play a key role for determining rupture size of subduction zone earthquakes.